Stability and collapse of fermions in a binary dipolar boson-fermion 164Dy-161Dy mixture - Adhikari, S. K. [UNESP] (American Physical Society (APS), 2013)
We suggest a time-dependent mean-field hydrodynamic model for a binary dipolar boson-fermion mixture to study the stability and collapse of fermions in the 164Dy-161Dy mixture. The condition of stability of the dipolar mixture is illustrated in terms of phase diagrams. A collapse is induced in a disk-shaped stable binary mixture by jumping the interspecies contact interaction from repulsive to attractive by the Feshbach resonance technique. The subsequent dynamics is studied by solving the time-dependent mean-field model including three-body loss due to molecule formation in boson-fermion and boson-boson channels. Collapse and fragmentation in the fermions after subsequent explosions are illustrated. The anisotropic dipolar interaction leads to anisotropic fermionic density distribution during collapse. This study is carried out in three-dimensional space using realistic values of dipolar and contact interactions. © 2013 American Physical Society.